Desempenho da Gestão Organizacional dos serviços hospitalares do Brasil: uma avaliação segundo o Programa Nacional de Avaliação de Serviços de Saúde (PNASS) - Letícia Ferreira da Silva Machado (2021)
ABSTRACT Introduction: To evaluate the performance of the Organizational Management of Hospital Services in Brazil is relevant because the organizational management actions provide adequate operation, planning, and organization to hospitals as well as physical, technological, material, and human conditions that influence the care results. Considering the large number of hospitals that are part of the Brazilian Unified Health System and the importance of these services in the population health care, it becomes relevant to evaluate them from an organizational management standpoint. Objective: To evaluate the performance of the Organizational Management of Hospital Services in Brazil. Method: Cross-sectional study that used secondary data from the 2015-2016 National Health Services Evaluation Program to evaluate the Organizational Management Performance of 1665 hospitals in Brazil from 30 verification items referring to Contract Management, People, Information, Planning and Organization, Organizational Model, which constituted an evaluation score of the hospitals. The Performance was evaluated according to the indicators: hospital size, level of complexity, administrative system, type of management and region of the country. It was verified the association between Performance of Organizational Management of hospitals with indicators such as: Occupancy Rate, Average Length of Stay, Hospital Mortality Rate and Average Value of Hospital Admission Rate. We used Main Components Analysis in order to verify the dependent relationship among variables and to explain data variability. The adjusted logistic regression model was estimated to verify the variables that best explain the Organizational Management Performance. Results: The average of Organizational Management Performance of the hospitals was 63.83. In the evaluation by criteria the following results were obtained: Information Management (77.59), People Management (61.96), Contract Management (61.71), Organizational Model (61.64), Planning and Organization (56.45). The best results were seen in hospitals in the South region, Complexity level 8, above 150 beds, Federal Public Administrative System and State Management. In the logistic regression analysis the variables that most explain Organizational Management Performance are: Occupancy Rate (p<9.87E-09), Hospital Size (p<4.49E-10), Municipal Management (p<0.004), Hierarchical Level- Level 7 (p<0.042), Level 8 (p<0.022) Southern region (p<0.004), Southeast (p<0.002). Conclusion: The study shows that the PNASS is a powerful and qualified instrument for evaluating hospitals. Important gaps in the Organizational Management of Hospitals in relation to the PNASS criteria were highlighted. It also points to the relationship between scale and efficiency. Moreover, the study reinforces the regional inequality by concentrating hospitals in the South and Southeast regions in quantitative and qualitative terms, besides demonstrating the need for further study on the management of hospitals under municipal management given its insufficiency indicated in this study.